Developing Smart Apps Creator (SAC) Learning Media on Human Life Materials in the Pre-Literacy Period - Ilah Armilah; Pargito; Novia Fitri Istiawati; Dedy Miswar (International Journal of Advance Social Sciences and Education (IJASSE), 2024)
This type of research is R&D (Research and Development) research and development which is used to produce certain products and test the feasibility of the product before being disseminated. This research aims to develop Smart Apps Creator (SAC) learning media which contains material on the Life of Indonesian Society during the Pre-Literacy period. In this research, researchers will use the ADDIE R&D (Research and Development) development model from Robert Maribe Branch with five development stages, namely: Analyze, Design, Develop, Implement and Evaluate. Based on the results of product validation test results calculated by Media & Design Experts, a score of 84% was obtained, which means that the SAC Learning Media product has the criteria of Very Good and Suitable for Use. Meanwhile, based on the calculation results of the product validation test results by the Materials Expert, a value of 86.36% was obtained, which means that the SAC Learning Media product has the criteria of Very Good and Suitable for Use. So the conclusion of this research is that the Smart Apps Creator (SAC) Learning Media Product is suitable for use.